A novel cohorting and isolation strategy for suspected COVID-19 cases during a pandemic. Issue 4 (August 2020) - Patterson, B.; Marks, M.; Martinez-Garcia, G.; Bidwell, G.; Luintel, A.; Ludwig, D.; Parks, T.; Gothard, P.; Thomas, R.; Logan, S.; Shaw, K.; Stone, N.; et al.
SUMMARY: Background: The COVID-19 pandemic presents a significant infection prevention and control challenge. The admission of large numbers of patients with suspected COVID-19 disease risks overwhelming the capacity to protect other patients from exposure. The delay between clinical suspicion and confirmatory testing adds to the complexity of the problem. Methods: We implemented a triage tool aimed at minimizing hospital-acquired COVID-19 particularly in patients at risk of severe disease. Patients were allocated to triage categories defined by likelihood of COVID-19 and risk of a poor outcome. Category A (low-likelihood; high-risk), B (high-likelihood; high-risk), C (high-likelihood; low-risk) and D (low-likelihood; low-risk). This determined the order of priority for isolation in single-occupancy rooms with Category A the highest. Patients in other groups were cohorted when isolation capacity was limited with additional interventions to reduce transmission. Results: Ninety-three patients were evaluated with 79 (85%) receiving a COVID-19 diagnosis during their admission. Of those without a COVID-19 diagnosis: 10 were initially triaged to Category A; 0 to B; 1 to C and 4 to D. All high-risk patients requiring isolation were, therefore, admitted to single-occupancy rooms and protected from exposure. Twenty-eight (30%) suspected COVID-19 patients were evaluated to be low risk (groups C and D) and eligible for cohorting. No symptomatic hospital-acquired infections were detected in the cohorted patients. Discussion: Application of a clinical triage tool to guide isolation and cohorting decisions may reduce the risk of hospital-acquired transmission of COVID-19 especially to individuals at the greatest of risk of severe disease.